Strategy for Rapid Detection of Carbapenemase-Producing Enterobacteriaceae - Dortet, Laurent (American Society for Microbiology, 2014)
A prospective survey was conducted on 862 Enterobacteriaceae isolates with reduced susceptibility to carbapenems. The Carba NP test, UV spectrophotometry, and a DNA microarray were used to detect carbapenemase producers, and the results were compared to those from PCR and sequencing. The 172 carbapenemase producers were detected using the Carba NP test and UV spectrophotometry, whereas the DNA microarray failed to detect IMI producers. The use of the Carba NP test as a first screening, followed by the use of molecular techniques, has been determined to be an efficient strategy for identifying carbapenemase-producing Enterobacteriaceae.